Signaling mechanisms in mirror image pain pathogenesis - Jancalek, Radim (Annals of neurosciences, 2011)
It is now clear that a peripheral nerve lesion affects contralateral non-lesioned structures, and thus such a lesion can result in mirror image pain. The pathogenesis is still not exactly known, but there are some possible signaling pathways in the contralateral reaction of the nerve tissue after unilateral nerve injury. Potential signaling pathways of contralateral changes can be generally divided into humoral and neuronal mechanisms. Damage to peripheral nerves or spinal roots produces a number of breakdown products with development of an aseptic inflammatory reaction. Released immunomodulatory cytokines are believed to be transported via blood or cerebrospinal fluid into the contralateral part of the body affecting spinal roots, dorsal root ganglia or peripheral nerves. Because neurons are elements of a highly organized network, injury to the peripheral neuron results in signals that travel transneuronally into the central nervous system and affects the contralateral homonymous neurons. There is also evidence that spinal glia creates and maintain pathological pain. Additionally, there may be compensatory changes in behavior of animals with an impact on contralateral neurons, such as altered stance and motor performance or autonomic reflex changes. Although the transneuronal signaling pathway appears to be plausible, the humoral signaling pathway or other communication systems cannot be excluded at this time. Knowledge about these processes has clinical implications for the understanding of chronic neuropathic pain states, and, therefore, further studies will be necessary. Understanding signaling mechanisms in mirror image pain pathogenesis may provide novel therapeutic targets for the management of neuropathic pain.
Keywords: nerve injury; glia; cytokines; contralateral reaction; neurons